Implementation of Health Logistics Management System at Syahrul Husada Clinic - Hasibuan, Rapotan; Saragih, Devi Herdini; Wulandari, Putri Cahya; Hagareninsa, Clarissa Adisty; Haqiqi, Nasywa Nathania; Indah, Nurul; Berutu, Siti Sarah; Lubis, Amru Prabowo (PROMOTOR, 2025)
The implementation of a Health Logistics Management System at Syahrul Husada Clinic, which aims to improve the efficiency and effectiveness of health service delivery. The study identified several important areas for improvement, including the need for greater transparency in budget management, improved coordination in medical waste management, and ongoing training for medical staff to ensure safe and efficient logistics distribution. The findings show that while clinics have made strides in complying with regulatory standards for drug management, challenges remain in managing medical waste and ensuring timely disposal. Collaboration with third-party waste management services is essential to address these issues. The study emphasizes the importance of leveraging technology, such as cloud-based information systems, to predict logistics needs and support accurate planning. Overall, this study highlights the need to adhere to established procedures and protocols to maintain the quality and availability of healthcare logistics in clinics.